Characteristics of Co/Cr Codoped Zinc Oxide - N. Aljawfi, Rezq; Mollah, S. (Asian Journal of Chemistry, 2011)
In the present paper, we report the optical and magnetic properties of Zn0.97Co0.03O and Zn0.94Cr0.03Co0.03O, nanocrystalline powder diluted magnetic semiconductor, prepared by the sol-gel method. XRD patterns of the sample was indexed as hexagonal wurizite structure, the size of particles are 19 nm and 15 nm, respectively. UV-VIS optical absorption spectra results show that the band gap energy of the oxide semiconductor ZnO decrease with incorporation of Co and Cr in the ZnO lattice structure. Magnetic measurements performed by SQUID magnetometer reveals the presence of room temperature ferromagnetism.